Asymmetric synthesis and biological evaluation of (+)-cardiobutanolide, (−)-3-deoxycardiobutanolide and analogues as antiproliferative agents. (24th September 2021) - Kovačević, Ivana; Kesić, Jelena; Popsavin, Mirjana; Francuz, Jovana; Kojić, Vesna; Jakimov, Dimitar; Rodić, Marko V.; Zelenović, Bojana Srećo; Benedeković, Goran; Popsavin, Velimir
Abstract: Two natural products, (+)-cardiobutanolide and (−)-3-deoxycardiobutanolide, as well as five new analogues, were synthesized in several steps that included zinc-mediated THF ring opening, subsequent stereoselective olefination, and final Sharpless asymmetric dihydroxylation. In vitro antitumour activities of these compounds were evaluated against a panel of eight human tumour cell lines and one normal cell line. Some of compounds displayed powerful effects against tumour cells, but none of them were active toward normal cells. A SAR study revealed that the change of configuration at the C-6 and C-7 position of (+)-cardiobutanolide decreases antitumour activity of analogues. It also appears that the presence of a hydroxyl group at the C-3 position increases the activity of this type of lactones. A comparison of activities of conformationally rigid lactone goniofufurone with that of more flexible cardiobutanolide and 3-deoxycardiobutanolide indicates that steric flexibility has a positive effect on cytotoxicity. It was also confirmed that removal of the phenyl group may result in analogues of higher activity. Flow cytometry analysis revealed that the synthesized compounds did not induce apoptosis and necrosis of K562 cells. However, Western blot analysis showed that all compounds but one had an increased Bax/Bcl-2 protein expression ratio. Graphical abstract: Image 1 Highlights: New total synthesis of cardiobutanolide and 3-deoxycardiobutanolide was achieved. Several new analogues of these natural products were synthesized. Anti-proliferative activity of natural products and analogues has been recorded. SAR analysis revealed the structural features responsible for potent activities.